Intermolecular Singlet Fission in Unsymmetrical Derivatives of Pentacene in Solution. Issue 2 (16th November 2018) - Casillas, Rubén; Adam, Matthias; Coto, Pedro B.; Waterloo, Andreas R.; Zirzlmeier, Johannes; Reddy, Seelam Rajagopala; Hampel, Frank; McDonald, Robert; Tykwinski, Rik R.; Thoss, Michael; Guldi, Dirk M.
Abstract: Intermolecular singlet fission (SF) is an electronically coupled process between two chromophores, where distance dependences are decisive in terms of rates and yields. In the current work, a family of pentacene derivatives featuring different functional groups have been designed, synthesized, and probed with respect to intermolecular SF in the low, medium, and high concentration regimes rather than in the solid state. By means of advanced photophysical techniques, global analysis modeling, and ab initio calculations, a model for intermolecular SF is postulated. The model is based on an early key intermediate, which involves the diffusional encounter between one pentacene in its singlet excited‐state with another one in its ground state and which features excimer characteristics. This is followed by a transformation into a coupled triplet excited‐state. The role of the functional group appended to pentacene is analyzed with respect to steric shielding of the pentacene core as a means to prevent photophysical degradation, as well as control diffusional encounter and, subsequently, SF. The findings demonstrate the potential of new molecular materials for SF, especially in solution studies, as well as the challenges of implementing them in energy conversion schemes due to the appearance of photodegradation processes that compete with SF. Abstract : By means of advanced photophysical techniques, global analysis modeling, and ab initio calculations, an early key intermediate for intermolecular singlet fission is postulated. It involves the diffusional encounter between one pentacene in its singlet excited‐state with another one in its ground state and features excimer characteristics.